Assessing the microbial diversity and proximate composition of smoked-fermented bushmeat from four different bushmeat samples - Afia Sakyiwaa Amponsah; Gloria Mathanda Ankar-Brewoo; Herman Erick Lutterodt; Isaac Williams Ofosu (BioTechnologia, 2024)
The ever-increasing demand for wildlife-derived raw or processed meat commonly known as bushmeat, has been identified as one of the critical factors driving the emergence of infectious diseases. This study focused on examining the bacterial community composition of smoked and fermented bushmeats, specifically grasscutter, rat, rabbit, and mona monkey. The analysis involved exploring 16Sr RNA amplicon sequences isolated from bushmeat using QIIME2. Microbiome profiles and their correlation with proximate components (PLS regression) were computed in STAMP and XLSTAT, respectively. Results indicate the predominance of Firmicutes (70.9%), Actinobacteria (18.58%), and Proteobacteria (9.12%) in bushmeat samples at the phylum level. Staphylococcus, Arthrobacter, Macrococcus , and Proteus constituted the core microbiomes in bushmeat samples, ranked in descending order. Notably, significant differences were observed between the bacterial communities of bushmeat obtained from omnivores and herbivores (rat and mona monkey, and grasscutter and mona monkey), as well as those with similar feeding habits (rat and monkey, and grasscutter and rabbit) at the family and genus levels. Each type of bushmeat possessed unique microbial diversity, with some proximate components such as fat in rat samples correlating with Staphylococcus , while proteins in Mona monkey correlated with Arthrobacter and Brevibacterium , respectively. The study underscores public health concerns and highlights probiotic benefits, as bushmeat samples contained both pathogenic and beneficial bacteria. Therefore, future research efforts could focus on improving bushmeat quality.